Prescribing practices for psychiatric intensive care during COVID-19. (1st September 2020) - Butler, Margaret; Harries, Bethan; Skelton, Luke; Vallianatou, Kalliopi; Blake, Lucy; Pugh, Ria; Sethi, Faisil
This series of brief reports highlights the experience of a London psychiatric intensive care unit (PICU) that had multiple cases of COVID-19 relatively early in the pandemic. The objective is to contribute to learning and consider future challenges for psychiatric intensive care services. This article will outline how the PICU adapted to the rapidly changing situation with consideration of prescribing in COVID-19 and the unique challenges faced by PICU services.